GPKOW is essential for pre-mRNA splicing in vitro and suppresses splicing defect caused by dominant-negative DHX16 mutation in vivo. Issue 6 (12th December 2014) - Zang, Shengbing; Lin, Ting-Yu; Chen, Xinji; Gencheva, Marieta; Newo, Alain N. S.; Yang, Lixin; Rossi, Daniel; Hu, Jianda; Lin, Shwu-Bin; Huang, Aimin; Lin, Ren-Jang
Abstract : Using biochemical, mutation, and cellular analyses, we characterized important domains involved in the functionality of a RNA-binding protein in RNA splicing. We also showed the similarity and difference between yeast and human counterparts. Abstract : Human GPKOW [G-patch (glycine-rich) domain and KOW (Kyrpides, Ouzounis and Woese) domain] protein contains a G-patch domain and two KOW domains, and is a homologue of Arabidopsis MOS2 and Saccharomyces Spp2 protein. GPKOW is found in the human spliceosome, but its role in pre-mRNA splicing remains to be elucidated. In this report, we showed that GPKOW interacted directly with the DHX16/hPRP2 and with RNA. Immuno-depletion of GPKOW from HeLa nuclear extracts resulted in an inactive spliceosome that still bound DHX16. Adding back recombinant GPKOW restored splicing to the depleted extract. In vivo, overexpression of GPKOW partially suppressed the splicing defect observed in dominant-negative DHX16 mutant expressing cells. Mutations at the G-patch domain greatly diminished the GPKOW–DHX16 interaction; however, the mutant was active in splicing and was able to suppress splicing defect. Mutations at the KOW1 domain slightly altered the GPKOW–RNA interaction, but the mutant was less functional in vitro and in vivo . Our results indicated that GPKOW can functionally impact DHX16 but that interaction between the proteins is not required for this activity.